An adaptive Newton multigrid method for a model of marine ice sheets - Jouvet, Guillaume; Gräser, Carsten (2012)
In this paper, we consider a model for the time evolution of marine ice sheets. This model combines the Shallow Ice Approximation (SIA) for the ice deformation, the Shallow Shelf Approximation (SSA) for the basal sliding and the mass conservation principle. At each time step, we solve a generalized p-Laplace minimization-type problem with obstacle (SIA), a vectorial p-Laplace minimization-type problem (SSA) and a transport equation (mass conservation). The two minimization problems are solved using a truncated nonsmooth Newton multigrid method while the transport equation is solved using a vertex-centred finite volume method. Our approach is combined to a mesh adaptive refinement procedure to face the large gradients of the solution that are expected close to the grounding line which separates the ice sheet and the ice shelf. As applications, we present some simulations of the marine ice sheet model inter- comparison project MISMIP in two and three space dimensions. In particular, we test the ability of our model to reproduce a reversible grounding line after being perturbed in model parameters.